Navigating non-sense by exemplifying situated life experience and intergenerational heritage knowledge in Education for Sustainable Development learning spaces - Rob O'Donoghue; Esther Kibuka-Sebitosi; Sirkka Tshiningayamwe; Carl Palmer (Environmental Association of Southern Africa, 2019)
The method which people use in acquiring knowledge is functionally interdependent with, and thus inseparable from, the substance of the knowledge they possess, and especially from their basic image of the world. If this image is different, the method they devise for acquiring knowledge is, as a matter of course, different too. (Elias, 1978:64) This paper uses an activity system perspective to probe the related problems of knowledge abstraction and a lack of relevance as a modern legacy of colonial education practices in Africa. Its purpose is to contemplate Education for Sustainable Development (ESD) pedagogy to support learning that might be better situated in and resonate with local African contexts and the emerging sustainability concerns in everyday life. Colonial education trajectories and the recent inclusion of new environmental knowledge in African curriculum and civic learning contexts are examined. This points to how circulating environment and sustainability knowledge is being constituted in disciplinary fields as abstract concepts that are often difficult to relate to local sustainability concerns. Socio-cultural heritage and intergenerational meaning making are explored to uncover better situated ways of navigating much of the abstract 'non-sense' confronting African learners in many modern education contexts today. Illustrative examples of historical patterns of exclusion are scoped and two cases of pedagogical innovation are examined to contemplate how to navigate better situated and more relevant learning processes. Enacted in situated and co-engaged ways, ESD practices may enable the socio-cultural capital and environmental realities of local social-ecological contexts to articulate with better situated sustainability propositions for transitioning to more peaceful, just and sustainable futures.